N Generalized Conharmonic Curvature Tensor Of The Locally Conformal Kahler Manifold - et. al., LHAM MAWLOD MOHAMMED, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, the geometrical properties of one of the almost Hermation manifold classes have been studied. In particular, we study generalized conharmonic curvature tensor ( GC curvature tensor) in some aspects Hermeation manifold ( in particular Of the Locally Conformal Kahler manifold (LCK- manifold) .The main results of this study are stated below:- 1) Proved that this tensor possesses the classical symmetry properties of the Riemannian curvature . 2) Computing components of generalized conharmonic curvature tensor ( GC curvature tensor) in LCK- manifold . 3) Got some results and establish relationships between the components of the tensor in this manifold.